OVERVIEW OF BACTERIAL PATTERNS IN TABANAN GENERAL HOSPITAL - Dewi, Sri Ratna; Diah witari, Diah; pradnyadari, Ayu; kahari, Siska (Meditory : The Journal of Medical Laboratory, 2023)
AbstractBackground: Resistant bacterial infections will affect the results of therapy, costs, spread of disease, and duration of illness. To minimize the losses incurred, it is necessary to monitor resistant bacterial and the use of antibiotics. Objective: To be able to identify, monitor, map and overcome antibiotic resistance and restrict bacterial transmission in hospitals, especially at the Tabanan General Hospital. Method: This research was conducted using a cross-sectional method using samples of inpatients and outpatients sent by clinicians to the Clinical Pathology Laboratory, Microbiology Sub Lab in period of January to December 2022. Results: Of the 590 positive culture samples in 2022, the majority were caused by Escherichia coli (15.25%) and 62.22% were ESBL. Apart from that, 8.31% were found to be Staphylococcus aureus and 53.06% were MRSA. Conclusion: The percentage of Escherichia coli bacteria that produce the ESBL enzyme is still high (62.22%). The percentage of Staphylococcus aureus bacteria that produce the MRSA enzyme is still high (53.06%). The antibiotics Meropenem, Amikacin, and Tigecycline are the antibiotics with the highest sensitivity to ESBL. The antibiotics Nitrofurantoin, Linezolid, and Quinupristin/Dalfopristin are the antibiotics with the highest sensitivity to MRSA. Keywords: bacterial patterns, description of bacterial distribution, antibiotic resistance